Graph-Based Model Reduction of the Controlled Consensus Protocol*. Issue 1 (July 2017) - Leiter, Noam; Zelazo, Daniel
Abstract: We present a general framework for graph-based model reduction of the controlled consensus protocol, and derive a class of edge-based graph contractions as a constructive solution approach. These contractions are utilized in a sub-optimal tree-based greedy-edge reduction method and are demonstrated on the H2 reduction of the controlled consensus protocol.